Rosacea – clinical variants and treatment - Czarnecka, Anna; Tymicka, Jolanta (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2005)
Rosacea is a common chronic dermatosis which occurs mainly in middle-aged patients. The etiology of the disease remains unknown but immune and vascular factors seen to play a crucial role. Diagnosis is established based on clinical manifestation. We present the actual classification of clinical variants, pathogenesis and therapy options of the disease.